Dermaphis coccidiformis sp. nov. (Hemiptera), an aphid species with asymmetrically sclerotized apterae and "winter alates". Issue 2 (23rd December 2017) - Aoki, Shigeyuki; Kurosu, Utako; Uematsu, Keigo; Fukatsu, Takema; Kutsukake, Mayako
Abstract: Dermaphis coccidiformis sp. nov. (Hormaphidinae: Nipponaphidini) is described from Japan. Apterous adults of the species were found between winter buds (or between a winter bud and a leaf petiole) of the evergreen oaks Quercus glauca, Q. myrsinifolia and Q. salicina . Their morphology is peculiar in that their tergites are heavily sclerotized only in the part that seems to have been exposed to sunlight. The new species is also peculiar in that nymphs to be alates (sexuparae) were found on the upper surfaces of leaves of the host oak only during winter, from December to March or early April, before the bud break of the oak. Our molecular phylogenetic analysis indicated that the new species is closely related to Dermaphis spp., therefore it was placed in the genus. The analysis incidentally indicated that "Dinipponaphis" autumna, a monoecious species forming galls on Distylium racemosum, was included in the clade of the genus Dermaphis, and therefore it was transferred to this genus. Abstract : Dermaphis coccidiformis sp. nov. (Hormaphidinae, Nipponaphidini) with tiny but bizarre apterous adults, whose exoskeletons are irregularly and in most cases asymmetrically sclerotized and which live between winter buds of the evergreen oak Quercus glauca, is described from Japan. This aphid species is also peculiar in that alate sexuparae are produced only during winter, before the bud break of the host oak.